2016
DOI: 10.1016/j.mrgentox.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

In vitro comet and micronucleus assays do not predict morphological transforming effects of silica particles in Syrian Hamster Embryo cells

Abstract: Crystalline silica particles and asbestos have both been classified as carcinogenic by the International Agency for Research on Cancer (IARC). However, because of the limited data available, amorphous silica was not classifiable. In vitro, the carcinogenic potential of natural crystalline and amorphous silica particles has been revealed by the Syrian Hamster Embryo (SHE) cell transformation assay. On the other hand, the genotoxic potential of those substances has not been investigated in SHE cells. And yet, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…However, macrophages are not considered relevant as surrogate target cells to evaluate genotoxic damage to the lung [ 6 ]. In addition, MN and comet results do not correlate with particle induced carcinogenicity as demonstrated by Darne et al [ 24 ]. They studied MN and comet induction in Syrian hamster embryo (SHE) cells, and in Chinese hamster lung (V79) cells, to evaluate the genotoxicity of quartz (Min-U-Sil, fully crystallised), commercial cristobalite (Chd, partly crystallised) and chrysotile (asbestos) as known carcinogens, and diatomaceous earth (DE, 100% amorphous) as control.…”
Section: Methodsmentioning
confidence: 89%
“…However, macrophages are not considered relevant as surrogate target cells to evaluate genotoxic damage to the lung [ 6 ]. In addition, MN and comet results do not correlate with particle induced carcinogenicity as demonstrated by Darne et al [ 24 ]. They studied MN and comet induction in Syrian hamster embryo (SHE) cells, and in Chinese hamster lung (V79) cells, to evaluate the genotoxicity of quartz (Min-U-Sil, fully crystallised), commercial cristobalite (Chd, partly crystallised) and chrysotile (asbestos) as known carcinogens, and diatomaceous earth (DE, 100% amorphous) as control.…”
Section: Methodsmentioning
confidence: 89%
“…Accordingly, we investigated the effect of a nano-silica particle, NM-203, on Bhas 42 cells. In parallel, we also tested a crystalline silica microparticle, Min-U-Sil® 5, known for its transforming and carcinogenic properties (Darne et al, 2016). In a previous work, we observed that both particles induced Bhas 42 cell transformation in the promotion assay (Fontana et al, In press).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, silica particles can induce oxidative stress leading to DNA damage and are responsible for gene silencing through DNA methylation of genes involved in cell cycle regulation (Belinsky et al, 2002, Deshpande et al, 2002, Knaapen et al, 2002. While treatment by the crystalline silica microparticle Min-U-Sil® 5 induced in vitro neoplastic transformation, treatment by amorphous silica nanoparticles did not induce BALB/3T3 or SHE cell transformation (Darne et al, 2016, Saffiotti and Ahmed, 1995, Uboldi et al, 2012. However, recent studies described that synthetic amorphous silica nanoparticles induce in in vitro models oxidative stress and genotoxic effects or in in vivo models cellular cell death and fibrosis , Murugadoss et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the suitability of the Bhas 42 CTA for particle-type substances was assessed using crystalline (quartz Min-U-Sil 5) and amorphous (diatomaceous earth) silica microparticles that have been previously evaluated for their transforming activity in the Syrian hamster embryonic (SHE) CTA [17,18]. [19] (Table 1).…”
Section: Introductionmentioning
confidence: 99%